(untitled) (Bangladesh Journal of Neuroscience, 2013)
Stroke is the third most common cause of mortality in Westernised countries and Accounts for 12% of all deaths in the UK. The economic cost of stroke is enormous. Twelve per cent of first strokes occur in patients under 45 years of age, of which approximately 50% are ischaemic in nature. Stroke in young adult poses a major health problem. The causes of ischaemic stroke in young adults are many and diverse.Such patients usually require more extensive investigations in order to find an underlying cause than more elderly patients. Principal causes are cardioembolism, premature atherosclerosis, haematological and immunological disorders and migraine. Thrombophilic factors have been implicated in 4-8% of the young adult strokes worldwide. Protein S deficiency is a rare cause of ischemic stroke in young population. Only a few sporadic cases have been described in the literature. We are reporting a case of protein S deficiencyrelated ischemic stroke in a 40-year-old man. Early diagnosis and targeted approach can help such patients to prevent recurrent thrombotic episodes. Bangladesh Journal of Neuroscience 2012; Vol. 28 (1): 59-62